Single B cell technologies for monoclonal antibody discovery. Issue 12 (December 2021) - Pedrioli, Alessandro; Oxenius, Annette
Abstract : Monoclonal antibodies (mAbs) are often selected from antigen-specific single B cells derived from different hosts, which are notably short-lived in ex vivo culture conditions and hence, arduous to interrogate. The development of several new techniques and protocols has facilitated the isolation and retrieval of antibody-coding sequences of antigen-specific B cells by also leveraging miniaturization of reaction volumes. Alternatively, mAbs can be generated independently of antigen-specific B cells, comprising display technologies and, more recently, artificial intelligence-driven algorithms. Consequently, a considerable variety of techniques are used, raising the demand for better consolidation. In this review, we present and discuss the major techniques available to interrogate antigen-specific single B cells to isolate antigen-specific mAbs, including their main advantages and disadvantages. Highlights: Monoclonal antibodies (mAbs) are among the most important type of biologic drugs on the pharmaceutical market, as well as for diagnostic purposes. Presently, more than 100 mAbs have been approved by the US FDA against a variety of diseases such as cancer, infectious diseases, autoimmune diseases, and neurological disorders. Primary antigen-specific B cells are the main source for obtaining antigen-specific mAb sequences, particularly using human specimens such as peripheral blood mononuclear cells. Also, the humanization of mAbs derived from other species (e.g. mice, rats, and rabbits) has become easier and more efficient. Currently, single B cell screening systems bear multiple advantages over other systems, such as display technologies. Particularly, the in vivo development of mAbs favors the safety profile and the overall developability. It also has reduced off-target binding to the human proteome. Single B cell technologies have significantly evolved, becoming faster and higher throughput than before. Nonetheless, hybridoma technology, the first technique in this field, still represents an important methodology and is well known within the scientific community. At present no gold standard exists in the field, relying on a broad variety of different single B cell systems for mAb discovery – each with its advantages and disadvantages.